Tenofovir disoproxil fumarate rescue therapy following failure of both lamivudine and adefovir dipivoxil in chronic hepatitis B. Issue 2 (29th October 2010) - Patterson, S J; George, J; Strasser, S I; Lee, A U; Sievert, W; Nicoll, A J; Desmond, P V; Roberts, S K; Locarnini, S; Bowden, S; Angus, P W
Abstract : Objective: To determine the efficacy of tenofovir disoproxil fumarate (TDF) in adults with chronic hepatitis B virus (HBV) infection who had previously failed lamivudine (LAM) and had significant viral replication (HBV DNA >10 5  copies/ml if HBeAg positive, >10 4  copies/ml if HBeAg negative) despite at least 24 weeks of treatment with adefovir dipivoxil (ADV). Design: A prospective open-label study of TDF 300 mg daily. Patients receiving combination ADV/LAM prior to baseline were switched to TDF/LAM. Setting: Multiple tertiary referral centres. Methods: Sixty patients were enrolled. The median age was 48.5 years (range 21–80), 46 (77%) were male and 40 (67%) were HBeAg positive. Thirty-eight patients (63%) were switched from ADV to TDF, the remainder from ADV/LAM to TDF/LAM. At baseline, substitutions conferring resistance to LAM or ADV were present in 20 patients (33%) and 17 patients (28%), respectively. The median baseline viral load was 5.33 log10  IU/ml (range 2.81–8.04). Patients initially treated with TDF monotherapy with persistent viral replication at or after 24 weeks were switched to TDF/LAM. The main outcome measures were change in HBV viral load from baseline and percentage of patients achieving an undetectable viral load (<15 IU/ml). Results: Results are reported at 96 weeks of treatment. One patient discontinued TDF at 10 days due to rash. The time-weighted change in viral load from baseline to week 12 was −2.19 log10  IU/ml overall. The median change in HBV DNA from baseline to weeks 12, 24, 48 and 96 was −2.86, −3.23, −3.75 and −4.03 log10  IU/ml, respectively. At 48 and 96 weeks, 27/59 (46%) and 38/59 (64%) patients achieved a HBV DNA <15 IU/ml. The response was independent of baseline LAM therapy or mutations conferring ADV resistance. Conclusions: In heavily pretreated patients with a high rate of genotypic resistance, TDF retains significant activity against HBV although this appears diminished in comparison with studies of naïve patients.